Rehabilitation initiatives towards informal workers in commercial capture fisheries post typhoon haiyan the case of Estancia. - Novilla, Carmela Therese
Informal workers are made to live with everyday consequences of marginality. Their everyday politics is an attempt to connect and break their imperceptible presence with respect to formal government apparatuses. For instance, there is a current lack for post-disaster programs that cater to the informal economy. Their invisibility as a sector pushes them into exclusion from efforts designed for disaster-related recovery., This study looks into the various rehabilitation initiatives directed towards the informal workers of commercial capture fisheries in the municipality of Estancia following typhoon Haiyan. It traces how the notion of informality informs the rehabilitation effort by local government units and civil society organizations towards informal workers of the said industry. Using the Sustainable Livelihood Framework and Network Theory, key informant interviews were conducted among representatives from civil society organizations and local government units and 9 informal workers. Ten (10) informal workers grouped according to vessel were also chosen as respondents for the focus group discussion. The study argues that the rehabilitation initiatives were blind towards the informal sector of the commercial capture fisheries industry and the institutions. Agencies are found to be insensitive to the vulnerability context of the said industry.